Simulation of the fate of the insecticide carbofuran in a rice field using a level IV fugacity model - Paraiba, L.C.=700 1 De M. Plese, L.P.; Foloni, L.L.; Carrasco, J.M.
(Es, En)
ilus., 44 ref.
Keywords: CARBAMATOS; PLAGUICIDAS; ORYZA SATIVA; COLEOPTERA; CURCULIONIDAE; ESPAÑA; GORGOJOS; ORYZOFHAGUS ORYZAE